Determination of Nutrition Habits and Food Supply Changes During Covid-19 Pandemic - Nilgün Budak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The research aims to determine the changes that took place in the lifestyles and dietary and food purchasing habits of the Turkish population during the Covid-19 pandemic by considering regional distribution and age factors. A survey was applied in this study. The survey evaluated the participants' sociodemographic and anthropometric characteristics, dietary habits, food purchasing habits, and their daily, weekly, and monthly consumption of 22 different food items in terms of both the pre- and during-pandemic periods. The study enrolled 725 participants' between the ages 15-80, living in Turkey. The answers to the online questionnaire showed that there was an increase in their frequency of taking vitamin C and D, zinc, complex vitamins, fish oil, food supplements, buying packaged products, dairy products, probiotic supplements, fruits, seafood. While there was a decrease in the participants' smoking and alcohol consumption frequency, an increase in their daily sleep duration and gaining weight. Also, it was determined that online shopping increased by 166%, while local food market decreased by 41.12%. It has been determined that people should eat healthy and strengthen their immune system in epidemics. For this reason, it has been determined that the infrastructures of producers, carriers and sellers in the food supply chain should be improved in order to meet the needs of people.